Pengembangan Keterampilan Berpikir Tingkat Tinggi Melalui Pendekatan Open-Ended - I Wayan Januariawan; I Komang Wisnu Budi Wijaya; Ni Kadek Supadmini; Diah Nirmala Dewi (Jayapangus Press, 2020)
Nowadays industrial revolution era, High Order Thinking Skills (HOTS) is part of skills needed to face global rivalry and complex life challenges. However, these skills incline to be little-mastered. It seems to be necessary to develop Higher Order Thinking Skills from the early-ages, especially for students which are integrated in the learning process. This study is a kind of library research. The result of this study showed is the advancement of HOTS can be done through an open-ended approach. The open-ended approach is able to stimulate the students in getting used to think critically, logically, creatively, collusively, argumentating, until decision making in the form of problem solving which contains analyzing, evaluating, and creating activities. Thus, the open-ended approach is well done in the learning process that can support the development of Higher Order Thinking Skills (HOTS)